PENGARUH METODE MIND MAPPING TERHADAP PROSES BELAJAR BERPIKIR KREATIF IPAS PADA MATERI AYO BERKENALAN DENGAN BUMI KITA KELAS V - Putri Jayani Simbolon; Destrinelli; Risdalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the mind mapping method on the learning process of creative thinking in IPAS (Science and Social Science) in the topic "Let's Get to Know Our Earth," and to identify the stages of the creative thinking learning process. The research was conducted at SDN 197/IV Kota Jambi in Grade V. This study uses a quantitative research approach with a quasi-experimental design. Data collection techniques were carried out by administering essay tests. The data were then processed to compare the final measurements of the experimental class and the control class. The results of the study showed that the learning process of creative thinking in IPAS using the Mind Mapping method in Grade V was more effective than using the direct instruction method. The average final score obtained through the Mind Mapping method was 81.47, while the direct instruction method yielded an average score of 67.50. Based on the t-test, the calculated t-value (tₕ = 6.599) was greater than the t-table value (tₜ = 1.679). According to the test criteria, this indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (H₀) is rejected, confirming a significant difference between the mind mapping method and the direct instruction method. Based on these findings, it can be concluded that learning using the mind mapping method can enhance the creative thinking learning process in IPAS for Grade V students. Therefore, it can be used as an alternative teaching method for IPAS.